(untitled) (مجلة الواحات للبحوث والدراسات, 2017)
This Paper Seeks To Shed Light On The Book "Takhlis Alani" By Amhammad Atfyach (1323 AH) By Dealing With It From An Angle Unlike What Researchers Did Before. The Book Was Given Great Attention To The Accomplishment And The Issuance Of Texts As Well As A Group Of Researchers Studied The Book Within Its Scientific Material. (Dr. Mohammed Al-Saeed Bin Saad, Amhamed Lqdi, Dr. Fatima Small)However, No One Considered The Process Of Text Critical Edition, Which Is Fndamental Through Which Studies Begin To Reach Accurate Scientific Results. The Process Of Critical Edition Of The Text To The Publishing And Transmission Passes Through Successive Consecutive Stages, Reducing The Severity Of Errors Which Is Ineluctable In Any Work. The Release Of The Book "Takhlisalani" Calls For Reconsideration Of This Process Through Careful Tracking Of The Stages Of Scientific Investigation. Keywords - Atfyach, Rhetoric, Critical Edition, Apostille, Lacuna, Manuscripts.